The Relationship Between Dynamic Stability and Multidirectional Speed. Issue 11 (November 2016) - Lockie, Robert G.; Schultz, Adrian B.; Callaghan, Samuel J.; Jeffriess, Matthew D.
Abstract : Abstract: Lockie, RG, Schultz, AB, Callaghan, SJ, and Jeffriess, MD. The relationship between dynamic stability and multidirectional speed. J Strength Cond Res 30(11): 3033–3043, 2016—Dynamic stability is said to contribute to multidirectional (linear and change-of-direction) speed, although little research confirms this. This study analyzed the relationship between dynamic stability as measured by lower-limb functional reaching in 6 directions (anterolateral, lateral, posterolateral, posteromedial, medial, and anteromedial) within a modified star excursion balance test and multidirectional speed (40-m sprint: 0–10, 0–20, and 0–40 m intervals; T -test; change-of-direction and acceleration test [CODAT]). Sixteen male field sport athletes (age, 23.31 ± 5.34 years; height, 1.78 ± 0.07 m; mass, 80.60 ± 9.89 kg) completed testing. A 1-way analysis of variance determined significant ( p ⩽ 0.05) differences in excursions between faster and slower subjects. All data were pooled for a Spearman's correlation analysis ( p ⩽ 0.05). Faster subjects had greater left leg medial reach (76.24 ± 5.33 vs. 65.94 ± 10.75%), right leg posteromedial reach (85.20 ± 8.07 vs. 73.59 ± 12.64%), and a smaller between-leg difference in lateral reach (2.26 ± 1.85 vs. 6.46 ± 4.29%). Longer reach distances (greater dynamic stability) correlated with faster speed test times ( ρ = −0.499 to 0.664). Dynamic stability relationships were pronounced for the change-of-direction speed tests. For example, smaller between-leg excursion differences in anterolateral, lateral, posterolateral, and posteromedial reaches related to faster T -test and CODAT times ( ρ = 0.502–0.804). There is a relationship between dynamic stability as measured by functional reaching and multidirectional speed in field sport athletes, possibly because of similarities in movement demands and muscle recruitment. Dynamic stability training could strengthen muscles for multidirectional sprinting and develop functional joint motion.